Licea nemotatarica sp. nov.—a corticolous myxomycete from northern nemoral border of Eastern European boreal ecotone - Sadykov, Ruslan E.; Potapov, Kim O. (Phytotaxa, 2024)
A morphologically atypical corticuloid representative of Licea was discovered at the northern border of the distribution of broadleaved forests in Eastern Europe. The species, named L. nemotatarica, contains several morphological and ecological features that strongly distinguish it from similar species such as L. nigromarginata, L. tuberculata, L. mariae and L. castanea. These include the peculiar light silvery or golden-green colouring of the smooth spores, their relatively small size, the wavy fusion of the peridium plate, the concentration of granular material on the surface in the form of a relief pattern, and the fact that it lives in the slightly alkaline and neutral environment of the bark of deciduous trees. The species also does not spread outside the forest protection zone established by Emperor Peter the Great in the 18th century. Based on the calculation of spore productivity, we assume that the species inhabits primarily the bark of Quercus robur and Tilia cordata, and secondarily Acer platanoides and Populus tremula, where it becomes active only after reaching a certain alkalinity in the cultures during decomposition.